Mother tongue : the story of the English language - Bryson, Bill (Penguin, 2016)
'More than 300 million people in the world speak English and the rest, it sometimes seems, try to...' Only Bill Bryson could make a book about the English language so entertaining. With his boundless enthusiasm and restless eye for the absurd, this is his astonishing tour of English.